2005
DOI: 10.1007/s00774-004-0554-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of age on body sway assessed by computerized posturography

Abstract: The swaying and postural instability frequently seen in elderly subjects had not been analyzed quantitatively in detail until the introduction of computerized posturography. In order to assess the changes of body sway with aging, we performed computerized posturography in 144 subjects (51 men and 93 women, between the ages of 22 and 88 years) without specific neurological or metabolic disorders. The total and timed track length of the center of gravity, reflecting the distance of sway, increased with advancing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
1
12

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(59 citation statements)
references
References 11 publications
4
42
1
12
Order By: Relevance
“…This result is in agreement with previous studies showing that stability decreases with age: more aged less stable [25][26][27].…”
Section: Age Effectssupporting
confidence: 93%
See 1 more Smart Citation
“…This result is in agreement with previous studies showing that stability decreases with age: more aged less stable [25][26][27].…”
Section: Age Effectssupporting
confidence: 93%
“…From the literature [25][26][27][28], one can report that the stability of an individual deceases after 60 years old. When using the mPCA on rambling, two groups can be distinguished which is particularly interesting and promising.…”
Section: Age Effectsmentioning
confidence: 99%
“…Much of our knowledge about the relationship between vision and balance has been obtained largely by comparing eyes open and closed conditions, and observing the effects upon body sway (Uchida et al 1979;Hytonen et al 1993;Fujita et al 2005;Rougier and Garin 2006;Guerraz and Bronstein 2008;Uchiyama and Demura 2008). While it has been shown that older adults sway more in response to unexpected eye-movements (Speers et al 2002;van Wegen et al 2002;Monzani et al 2005), the relationship between postural configuration and eyemovement behaviour is not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…Em especial, com relação à área, idosos apresentaram maiores valores que jovens tanto na BSST quanto na BSN. Enquanto alguns trabalhos que analisaram jovens e idosos na base de suporte normal [14][15] encontraram diferença entre os valores de área de deslocamento do centro de pressão, corroborando o presente trabalho, outros estudos não encontraram diferença entre os dois grupos analisados 7,[16][17] . A maior área de oscilação postural pode refl etir a inefi cácia no controle postural e défi cit nos movimentos de ajuste fi no, o que poderia estar relacionado à má utilização da informação somatossensorial para corrigir as oscilações posturais, podendo refl etir atraso e imprecisão no feedback sensorial para detectar a posição do centro de massa 5 .…”
Section: Discussionunclassified